Fenomena Feminisme pada Film Marlina si Pembunuh dalam Empat Babak: Analisis Wacana Kritis Van Dijk - Syekhan Abdil Barr; Safila Mutiara Fani; Reenata Amodia Khansa; Fitri Mutia (Jurnal Spektrum Komunikasi, 2026)
This research investigates the formation of women's discourse in the film Marlina: The Murderer in Four Acts through the framework of Teun A. Van Dijk's Critical Discourse Analysis. It utilizes Critical Discourse Analysis to analyze the film's portrayal of gender-based violence in various facets, such as verbal, physical, psychological, and institutional dimensions, while underscoring the ways in which patriarchal norms marginalize women in rural areas. The study seeks to uncover how liberal feminist principles are expressed via the film's storyline, character autonomy, and socio-cultural backdrop. Employing qualitative descriptive approaches, the examination combines textual scrutiny, social cognition, and contextual factors, supported by interviews with two audience members. The results demonstrate that the film depicts women not solely as helpless sufferers but as empowered agents who can assert control over their bodily autonomy amid societal prejudices and restrictive legal systems. Marlina's defiance, paired with the movie's focus on themes of seclusion, systemic indifference, and dehumanization, exposes a narrative that challenges patriarchal dominance and advocates for fair judicial opportunities. Audience feedback confirms that ingrained societal prejudices force women into a dual struggle: evading harm and validating its occurrence. In essence, the film establishes a liberal feminist discourse that prioritizes personal empowerment, legal parity, and women's entitlement to self-governance.